Developing Critical Thinking in Digital Learning Environments: Challenges and Opportunities - Rokhmah, Trias Istina; Darsono, Darsono; Sucipto, Sucipto; Restian, Arina; AM, Ichsan Anshory (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aims to map existing research on critical thinking in digital learning environments by identifying reported challenges, opportunities, and pedagogical strategies.Methods – A scoping review was conducted following the framework of Arksey and O’Malley (2005). A systematic search of the Scopus database was performed using the keywords critical thinking, digital learning, online learning, and blended learning. After automated filtering, title screening, abstract screening, and full-text review, 20 peer-reviewed open-access journal articles published between 2020 and 2025 were included. Data were extracted and synthesized in relation to three research questions addressing challenges, opportunities, and pedagogical strategies. Findings – The review identified recurring challenges, including superficial integration of higher-order thinking, limited learner self-regulation, technological and institutional constraints, and assessment limitations. At the same time, digital learning environments offer opportunities through flexible access, authentic learning tasks, collaborative interaction, and metacognitive support. Pedagogical strategies such as inquiry-based, project-based, case-based, and flipped learning were consistently associated with positive critical thinking outcomes when supported by instructional alignment and scaffolding. Research Implications – The findings emphasize the central role of pedagogical design in fostering critical thinking through digital learning. As a scoping review, this study maps trends rather than evaluating intervention effectiveness and is limited to open-access Scopus-indexed articles.